2010
DOI: 10.1007/s12272-010-0802-4
|View full text |Cite
|
Sign up to set email alerts
|

Baimantuoluosides D-G, four new withanolide glucosides from the flower of Datura metel L.

Abstract: In our search for bioactive anti-psoriasis compounds from the flower of Datura metel L, we isolated four new withanolide glucosides, baimantuoluosides D, E, F and G (1-4). The structures of the new compounds are (5alpha,6alpha,7beta,22R)-5,6,7,27-tetrahydroxy-1-oxowitha-2,24-dien-27-O-beta-D-glucopyranoside (1), (5alpha,6beta,7alpha,22R)-5,6,7,27-tetrahydroxy-1-oxowitha-2,24-dien-27-O-beta-D-glucopyranoside (2), (5alpha,6beta,7alpha,12beta,22R)-5,6,7,12,27-pentahydroxy-1-oxowitha-2,24-dien-27-O-beta-D-glucopyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Withanolides have been studied for treating psoriasis as the main constituents of the effective part of flowers of D. metel [11,12]. Baimantuoluolines A-J, and baimantuoluosides A-H were also isolated and reported [8,[13][14][15][16][17][18]. However, the dry flowers of D. metel have the disadvantages of long florescence and low yield in comparison to its leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Withanolides have been studied for treating psoriasis as the main constituents of the effective part of flowers of D. metel [11,12]. Baimantuoluolines A-J, and baimantuoluosides A-H were also isolated and reported [8,[13][14][15][16][17][18]. However, the dry flowers of D. metel have the disadvantages of long florescence and low yield in comparison to its leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has extensively researched on chemical constituents and pharmacological activities for many years, including multiple parts of D. metel L. such as leaves, seeds. A variety of compounds such as alkaloids, flavonoids and withanolides have been isolated from the plant (Yang et al 2010a(Yang et al , 2010b(Yang et al , 2013Kuang et al 2011). We also found that the flowers of D. metel L. had effect of anti-inflammatory, anti-itch, anti-proliferative and some other pharmacological effects and the seeds have anti-proliferation and potential immune suppression activities ).…”
Section: Introductionmentioning
confidence: 65%
“…The double doublet at δ 3.47 (1H, dd , J = 10.9, 4.5 Hz) was characteristic for a 12 β -hydroxywithanolide [4]. H-22 resonated as a double triplet at δ 4.62 (1H, dt , J = 12.9, 3.4 Hz), revealing a R configuration at C-22 [5,6]. …”
Section: Resultsmentioning
confidence: 99%
“…Flos Daturae has been found to be rich in tropane alkaloids [2]. Besides, a number of withanolides have also been isolated from Flos Daturae [3,4,5,6,7,8]. Recently Flos Daturae has been used clinically for the treatment of psoriasis in China [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation